PENDAMPINGAN MASYRAKAT DALAM PROGRAM PERCEPATAN PENINGKATAN TATA GUNA AIR IRIGASI - Talamati, Bambang Herianto; Potabuga, Ridwan; Nugroho, Chandra Wisnu; Wullur, Varly Carnavale (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The irrigation water use program is a strategy to increase the distribution of clean water, both from underground and mountain sources. problems that are often encountered in the quantity and function as well as the quality of irrigation infrastructure that has experienced degradation. Community participation and initiative in realizing self-sufficiency in the management of irrigation water use is still very low, due to the lack of knowledge and insight in the community. This activity is a mentoring program for the community to improve irrigation water use with the mentoring method, which is made up of training and instructions for the implementation of irrigation water use programs in Moyag Village. Participants in the activity were farmer groups, the youth team, and the local community. The results obtained show that it can be seen that the assistance in making water reservoirs is going well, and with the participation of community groups, these shelters are intended as water terminals that will be distributed to various areas. water needs in various areas in Moyag Village. It was concluded that the Moyag Village community was greatly assisted by the assistance in increasing the use of irrigation water, the training not only broadened the knowledge and skills of the community but had increased the community’s independence in water availability